Disease detection at the 48‐month exit round of the HPV FOCAL cervical cancer screening trial in women per‐protocol eligible for routine screening. Issue 7 (4th July 2019) - Coldman, Andrew J.; van Niekerk, Dirk; Krajden, Mel; Smith, Laurie W.; Cook, Darrel; Gondara, Lovedeep; Ceballos, Kathy; Quinlan, David J.; Lee, Marette; Elwood‐Martin, Ruth; Gentile, Laura; Peacock, Stuart; et al.
Abstract : HPV FOCAL is a randomized control trial of cervical cancer screening. The intervention arm received baseline screening for high‐risk human papillomavirus (HPV) and the control arm received liquid‐based cytology (LBC) at baseline and 24 months. Both arms received 48‐month exit HPV and LBC cotesting. Exit results are presented for per‐protocol eligible (PPE) screened women. Participants were PPE at exit if they had completed all screening and recommended follow‐up and had not been diagnosed with cervical intraepithelial neoplasia Grade 2 or worse (CIN2+) earlier in the trial. Subgroups were identified based upon results at earlier trial screening. There were 9, 457 and 9, 552 and women aged 25–65 randomized to control and intervention and 7, 448 (77.8%) and 8, 281 (86.7%), respectively, were PPE and screened. Exit cotest results were similar ( p = 0.11) by arm for PPE and the relative rate (RR) of CIN2+ for intervention vs . control was RR = 0.83 (95% CI: 0.56–1.23). The RR for CIN2+ comparing intervention women baseline HPV negative to control women with negative cytology at baseline and at 24 months, was 0.68 (95% CI: 0.43–1.06). PPE women who had a negative or CIN1 colposcopy in earlier rounds had elevated rates (per 1, 000) of CIN2+ at exit, control 31 (95% CI: 14–65) and intervention 43 (95% CI: 25–73). Among PPE women HPV negative at exit LBC cotesting identified little CIN2+, Rate = 0.3 (95% CI: 0.1–0.7). This per‐protocol analysis found that screening with HPV using a 4‐year interval is as safe as LBC with a 2‐year screening interval. LBC screening in HPV negative women at exit identified few additional lesions. Abstract : What's new? Human papillomavirus (HPV) testing is a sensitive approach for detecting cervical intraepithelial neoplasia grade 2 and higher (CIN2+). However, whether HPV testing alone, with extended intervals between visits, is more effective than HPV testing and liquid‐based cytology (LBC) combined for cervical screening remains uncertain. Here, HPV testing every four years was found to be at least as effective as LBC every two years for CIN2+ identification. Moreover, women were more likely to comply with screening protocol when four‐year intervals were used, compared to two‐year intervals. Women with CIN1 at colposcopy and women initially HPV‐positive may require screening with both methods.